A control education software suite to bridge methodological and engineering aspects. Issue 2 (2020) - Leva, Alberto; Cimino, Chiara; Seva, Silvano
Abstract: Software obviously plays a relevant role in both control education and engineering. Methodology-centred tools help learning in the class and are also useful for high-level tasks in the profession. Engineering-centred ones are necessary for any realistically sized problem, and their comprehension helps designing efficient and well maintainable control applications. However, brutalising for brevity, the two sets of tools hardly intersect one another, and are most often addressed with very different educational viewpoints—and frequently with some under-emphasis on the engineering side if not for laboratory practice. This paper provides a reasoned overview of the scenario just sketched, and based on a long experience, proposes a coordinated set of tools, selected among well assessed and solidly maintained ones, to help the students bridge methodological and engineering aspects into a unitary forma mentis.